Factors That Influence Improvement in Numeracy, Reading, and Comprehension in the Context of a Numeracy Intervention - Dowker, Ann (Frontiers in Psychology, 2016)
In a randomized controlled trial 104 primary school children, who received an individualized numeracy intervention, Catch Up Numeracy, were compared with 100 children, who received matched-time teaching, and 107, who received business-as-usual teaching. They were assessed before and after intervention, on the Number Screening Test and on both the reading and comprehension components of the Salford Sentence Reading Test. Those who received the intervention improved significantly more than the controls in numeracy but not in reading or comprehension. Numeracy, reading and comprehension scores were significantly correlated. Both reading and numeracy predicted improvement in comprehension, but only comprehension predicted improvement in reading, and neither literacy measure predicted improvement in numeracy. Children eligible for free school meals scored lower than others on all pretests and post-tests, but did not differ in their levels of improvement. Age negatively predicted improvement in reading and comprehension, but not numeracy. Gender affected comprehension but not reading or numeracy.